France : Financial Sector Assessment Program-Technical Note-Select Topics in Financial Supervision and Oversight. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on select issues examines different aspects of supervision and oversight in the French financial system. This chapter focuses on the regulatory requirements and supervisory practices that are most relevant to financial stability. In response to Single Supervisory Mechanism initiatives, the French Prudential Supervision and Resolution Authority (ACPR) has sharpened its focus on governance issues, although business model and profitability risk remains the main challenge for the Less Significant Institutions (LSI) sector. The SSM's commitment to consistent high supervisory standards has shaped the ACPR's supervisory approach to LSIs in other important ways. Business model and profitability risk remains the main challenge for the LSI sector in France. As noted, earnings have been under pressure due to the persistent low interest rate environment and stiff competition within the banking sector. Similarly, the ACPR's assessment is that liquidity risk does not pose significant issues for the LSI sector in France.